The Relationship between Self-Efficacy and Family Social Support with the Psychological Well-Being of High School Students - Citra Bella Prawita; Nurfarhanah Nurfarhanah; Neviyarni Neviyarni; Rezki Hariko (Journal of Educational, Health and Community Psychology, 2024)
The psychological well-being felt by teenagers makes teenagers have more positive emotions within themselves and can foster a sense of life satisfaction and happiness, thereby reducing negative behavior and reducing feelings of depression.  This research aims to determine the relationship between self-efficacy and family social support on students' psychological well-being.  This research is correlational research.  The sample of this research consisted of 252 students.  The research results show that self-efficacy and family social support simultaneously (together) have a significant relationship with students' psychological well-being.  This finding was obtained based on a series of data analyzes that there is a strong relationship between self-efficacy and family social support on psychological well-being of 56.3%, then the variables of self-efficacy and family social support can explain students' psychological well-being of 31.7%.